Differential Locus Expansion Distinguishes Toxoplasmatinae Species and Closely Related Strains of Toxoplasma gondii - Yaw Adomako-Ankomah (American Society for Microbiology, 2014)
ABSTRACT Toxoplasma gondii is a human obligate intracellular parasite that has infected over 20% of the world population and has a vast intermediate host range compared to those of its nearest relatives Neospora caninum and Hammondia hammondi. While these 3 species have highly syntenic genomes (80 to 99%), in this study we examined and compared species-specific structural variations, specifically at loci that have undergone local (i.e., tandem) duplication and expansion. To do so, we used genomic sequence coverage analysis to identify and curate T. gondii and N. caninum loci that have undergone duplication and expansion (expanded loci [ELs]). The 53 T. gondii ELs are significantly enriched for genes with predicted signal sequences and single-exon genes and genes that are developmentally regulated at the transcriptional level. We validated 24 T. gondii ELs using comparative genomic hybridization; these data suggested significant copy number variation at these loci. High-molecular-weight Southern blotting for 3 T. gondii ELs revealed that copy number varies across T. gondii lineages and also between members of the same clonal lineage. Using similar methods, we identified 64 N. caninum ELs which were significantly enriched genes belonging to the SAG-related surface (SRS) antigen family. Moreover, there is significantly less overlap (30%) between the expanded gene sets in T. gondii and N. caninum than would be predicted by overall genomic synteny (81%). Consistent with this finding, only 59% of queried T. gondii ELs are similarly duplicated/expanded in H. hammondi despite over 99% genomic synteny between these species. IMPORTANCE Gene duplication, expansion, and diversification are a basis for phenotypic differences both within and between species. This study represents the first characterization of both the extent and degree of overlap in gene duplication and locus expansion across multiple apicomplexan parasite species. The most important finding of this study is that the locus duplications/expansions are quantitatively and qualitatively distinct, despite the high degree of genetic relatedness between the species. Given that these differential expansions are prominent species-specific genetic differences, they may also contribute to some of the more striking phenotypic differences between these species. More broadly, this work is important in providing further support for the idea that postspeciation selection events may have a dramatic impact on locus structure and copy number that overshadows selection on single-copy genes.